2020 IEEE 27th International Conference on Software Analysis, Evolution and Reengineering (SANER) 2020
DOI: 10.1109/saner48275.2020.9054824
|View full text |Cite
|
Sign up to set email alerts
|

On Relating Technical, Social Factors, and the Introduction of Bugs

Abstract: As collaborative coding environments make it easier to contribute to software projects, the number of developers involved in these projects keeps increasing. Consequently, making it more difficult for code reviewers to deal with harmful contributions. Collaborative environments like GitHub provide a rich source of data on developers' contribution, which can be used to extract information on technical (e.g., developers' experience) and social (e.g., interactions among developers) factors related to developers. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The process of building and maintaining software is often collaborative and social, including not only code but code comments, commit messages, pull requests, and code reviews, as well as bug reporting, issue discussing, and shared problemsolving [24]. Non-code trace data may include signals of technical debt [25], signs that a given code commit contains bugs [26], or serve as indicators of committed developers, a high-quality software project, or a healthy, sustainable project community [27,28,29]. Prior research has found that digital trace data capturing online community activity can provide significant insight into the study of software [27].…”
Section: Systematic Comparison Of Floss In Software Repositoriesmentioning
confidence: 99%
“…The process of building and maintaining software is often collaborative and social, including not only code but code comments, commit messages, pull requests, and code reviews, as well as bug reporting, issue discussing, and shared problemsolving [24]. Non-code trace data may include signals of technical debt [25], signs that a given code commit contains bugs [26], or serve as indicators of committed developers, a high-quality software project, or a healthy, sustainable project community [27,28,29]. Prior research has found that digital trace data capturing online community activity can provide significant insight into the study of software [27].…”
Section: Systematic Comparison Of Floss In Software Repositoriesmentioning
confidence: 99%
“…The relationship between social aspects and design decay has not been studied so far. In fact, most of the previous studies focus on investigating the relations of social aspects with code review [77,76], post-release defects [9,26,18], pull-request acceptance [10,59] or software vulnerabilities [42]. Despite this vast body of knowledge, as aforementioned, the literature still lacks empirical evidence about the influence of different social aspects on design decay.…”
Section: Problem Statement and Limitations Of Related Workmentioning
confidence: 99%
“…Relation of social aspects with quality. Regarding the relation of social aspects with software quality, we found some studies that investigate how social aspects are related with defects [9,11,18]. Falcão et al [18] investigated the relationship between social, technical factors, and the introduction of defects.…”
Section: Social Aspects On Open-source Environmentsmentioning
confidence: 99%
See 2 more Smart Citations